Respiratory modulations of cortical excitability and interictal spike timing in focal epilepsy: a case report - Daniel S. Kluger; Tim Erdbrügger; Christina Stier; Malte B. Höltershinken; Omid Abbasi; Martina Saltafossi; Kanjana Unnwongse; Tim Wehner; Jörg Wellmer; Joachim Gross; Carsten H. Wolters (Communications Medicine)
Abstract Background Brain activity in focal epilepsy is marked by a pronounced excitation-inhibition (E:I) imbalance and interictal epileptiform discharges (IEDs) observed in periods between recurrent seizures. As a marker of E:I balance, aperiodic neural activity and its underlying 1/f characteristic reflect the dynamic interplay of excitatory and inhibitory currents. Recent studies have independently assessed 1/f changes both in epilepsy and in the context of body-brain interactions in neurotypical individuals where the respiratory rhythm has emerged as a potential modulator of excitability states in the brain. Methods Here, we investigate respiration phase-locked modulations of E:I balance and their involvement in the timing of spike discharges in a case report of a 25 year-old focal epilepsy patient using magnetoencephalography (MEG). Results We show that i) respiration differentially modulates E:I balance in focal epilepsy compared to N = 40 neurotypical controls and ii) IED timing depends on both excitability and respiratory states. Conclusions These findings overall suggest an intricate interplay of respiration phase-locked changes in excitation and the consequential susceptibility for IED generation and we hope they will spark interest in subsequent work on body-brain coupling and E:I balance in epilepsy.